Attitudes of Women Regarding the Voluntary Interruption of Pregnancy. (16th January 2015) - Ferreira, Manuela; Fernandes, Bruno; Duarte, João; Chaves, Cláudia
Abstract: Problem Statement: The voluntary interruption of pregnancy has been a controversial topic in economically developed societies, covering multiple perspectives and mobilizing human, ethical, social, psychological, political, technical and economic. Research Questions: What are the attitudes of women regarding the voluntary interruption of pregnancy? Purpose of the Study: Analyse the influence of socio-demographic variables on attitudes, obstetric variables and attitudes regarding the voluntary interruption of pregnancy; investigate the influence of self-esteem in attitudes regarding the voluntary interruption of pregnancy; relate the variables of family and social context with attitudes regarding the voluntary interruption of pregnancy. Research Methods: A quantitative study, with 101 women who voluntarily interrupted their pregnancy in Portugal. Data collection through a questionnaire with socio-demographic and obstetric history component and Family Functionality (Smilkstein 1978, Azevedo & Matos, 1989); Self Esteem Scale (Rosenberg, 1965, Santos & Maia, 1999, 2003); Satisfaction with Social Support (Ribeiro, 1999); Satisfaction in Areas of Conjugal Life (Narciso & Costa, 1996). Findings: The women's ages ranged between 16 and 49 years, 61.4% were single / divorced, 48.3% are in their second pregnancy. In Social Support, "full intimacy", "total social support" and Satisfaction in areas of conjugal life, "sexuality" and "full autonomy", have predictive power (p < 0.05) over the attitudes of women regarding the voluntary interruption of pregnancy. Conclusions: The knowledge of the attitudes of women regarding the voluntary interruption of pregnancy, will produce reflections in the specialized care, in the context of family planning and preconception and psychological support, aiming for excellence of the practices in maternal health, obstetrics and gynaecology.